Pulmonary hematoidin deposition in a case of severe COVID19 pneumonia - Nada Shaker; Justin P. Rosenheck; Bryan A. Whitson; Konstantin Shilo (Elsevier, 2022)
A 59-year-old male with past medical history significant for hypertension, coronary artery disease, atrial fibrillation, hyperlipidemia, obesity, obstructive sleep apnea and deep vein thrombosis developed severe COVID19 pneumonia. His clinical course was noted for progressive respiratory failure that subsequently resulted in bilateral lung transplantation. Examination of the explanted lungs was notable for the presence of extensive grossly apparent bright yellow discolorations that histologically represented hematoidin deposits. The background lung was affected by diffuse alveolar damage, accompanied by infarcts and organizing thrombi. This case suggests that a combination of acute lung injury and thrombotic complications in severe COVID19 pneumonia can facilitate formation of pockets of anoxic environment leading to hematoidin deposition within lung tissue.